2000
DOI: 10.1007/s002130050071
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in ethanol, phencyclidine, and food-maintained behavior by naltrexone pretreatment in monkeys is enhanced by open economic conditions

Abstract: These results indicated that the economy under which drugs and food are self-administered is an important determinant of the effectiveness of naltrexone's ability to suppress drug- and food-reinforced behavior. The results also suggest that testing medications for drug abuse using a food control condition under a closed economy can bias the results toward a conclusion of selectivity of the treatment medication for drug-reinforced behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…In contrast, in the present study, increasing the response requirement during the seeking component did not alter drinking behavior once access to alcohol was obtained, with intake remaining relatively constant. Studies using a variety of procedures and a variety of species [rats: (Heyman, 1997;Heyman et al, 1999;Petry and Heyman, 1995;Williams and Woods, 2000), rhesus monkeys: (Carroll et al, 2000), humans: (Goudie et al, 2007;Sumnall et al, 2004)] have also demonstrated that alcohol intake is resistant to change, in that subjects will defend their alcohol intake despite large increases in response cost. That is, in economic terms, alcohol can be considered an ''inelastic'' commodity (Heyman, 2000).…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, in the present study, increasing the response requirement during the seeking component did not alter drinking behavior once access to alcohol was obtained, with intake remaining relatively constant. Studies using a variety of procedures and a variety of species [rats: (Heyman, 1997;Heyman et al, 1999;Petry and Heyman, 1995;Williams and Woods, 2000), rhesus monkeys: (Carroll et al, 2000), humans: (Goudie et al, 2007;Sumnall et al, 2004)] have also demonstrated that alcohol intake is resistant to change, in that subjects will defend their alcohol intake despite large increases in response cost. That is, in economic terms, alcohol can be considered an ''inelastic'' commodity (Heyman, 2000).…”
Section: Discussionmentioning
confidence: 95%
“…Recently, data consistent with this result were reported by Paronis (Paronis, ), where naltrexone (up to 10 mg·kg −1 ) had very modest effects on behaviour maintained by concurrent availability of milk and milk + ethanol in food‐restricted rats. Further, the ability of naltrexone to reduce ethanol‐ and food‐maintained responding diminishes as the availability of food or ethanol outside of the experimental session increases (Nestby et al ., ; Carroll et al ., ). In the present study, food was available after the session, while ethanol was not.…”
Section: Discussionmentioning
confidence: 97%
“…These measures are important because treatment effects can vary dramatically depending upon the economic context (e.g., price of drug, availability of nondrug substitutes) of drug self-administration (Comer et al, 1994;Carroll et al, 2000). For example, demand for a drug refers to the relationship between consumption of a drug and unit price (FR), or number of responses per milligram consumed.…”
Section: Discussionmentioning
confidence: 99%